The effectiveness of patient-tailored treatment for acute organophosphate poisoning - Chih-Chuan Lin; Dong-Zong Hung; Hsien-Yi Chen; Kuang-Hung Hsu (Biomedical Journal, 2016)
Background: To determine a new pralidoxime (PAM) treatment guideline based on the severity of acute organophosphate intoxication patients, APACHE II score, and dynamic changes in serum butyrylcholinesterase (BuChE) activity. Methods: This is a randomization trial. All patients received supportive care measurements and atropinization. Each enrolled patient was treated with 2 gm PAM intravenously as the loading dose. The control group was treated according to the WHO's recommended PAM regimen, and the experimental group was treated according to their APACHE II scores and dynamic changes in BuChE activity. If a patient's APACHE II score was ≧26 or there was no elevation in BuChE activity at the 12th hour when compared to the 6th, doses of 1 g/h PAM (i.e., doubled WHO's recommended PAM regimen) were given. The levels of the serum BuChE and red blood cells acetylcholinesterase and the serum PAM levels were also measured. Results: Forty-six organophosphate poisoning patients were enrolled in this study. There were 24 patients in the control group and 22 patients in the experimental group. The hazard ratio of death in the control group to that of the experimental group was 111.51 (95% CI: 1.17–1.613.45; p = 0.04). The RBC acetylcholinesterase level was elevated in the experimental group but was not in the control group. The experimental group did not exhibit a higher PAM blood level than did the control group. Conclusion: The use of PAM can be guided by patient severity. Thus, may help to improve the outcomes of organophosphate poisoning patients.